Construction of rylene near-infrared absorption dyes with azaperylene monoimide. (February 2020) - Zhao, Xiaohong; Chen, Xuanwen; Yuan, Zhongyi; Zhang, Haina; Luo, Guoliang; Hu, Yu; Chen, Yiwang
Abstract: Rylene NIR absorption dyes APMI-N ( λ max = 796 nm) and (APMI-K, λ max = 787 nm) with compact conjugation, and excellent solubility, were designed and synthesized. Acid/base sensitive dyes 3, 4, 6, and 7 were obtained as well. Their maximum absorption could be adjusted conveniently from 532 nm to 715 nm by adding acid or base in the solvent. Theoretical simulations indicate both protonation of carbonyl O and electron donating O − in perylene monoimide play a critical role in absorption changing of those dyes. Graphical abstract: Image 1 Highlights: Two perylene monoimide NIR absorption dyes APMI-N and APMI-K were synthesized, and exhibited good solubility and stability. Two pH-sensitive compound 4 and 7 were synthesized. Their maximum absorption can be adjusted from 530 nm to 715 nm. Theoretical simulations indicate both protonation of carbonyl O and electron donating O − in PMI lead absorption changing.